Entrepreneurial intention among generation z education self efficacy and attitude - Bintoro Bagus Purmono (Enrichment : Journal of Management, 2023)
This research will see how far the influence of entrepreneurial education, entrepreneurial self-efficacy, and entrepreneurial attitude on entrepreneurial intention in generation Z Indonesia. This study will use a causal design approach with structural equation modeling (SEM) as a statistical approach to testing the constructed constructs and hypotheses. The number of samples used in this study were 406 respondents from business activists at the age of Generation Z in Indonesia. The results of the study show that entrepreneurial education has a significant effect on entrepreneurial attitude, entrepreneurial self-efficacy, and entrepreneurial intention in generation Z Indonesia. Entrepreneurial self-efficacy was also found to have a significant effect on entrepreneurial attitude and entrepreneurial intention in Generation Z Indonesia. Entrepreneurial attitude also has a significant influence on entrepreneurial intention in Indonesia's Z generation. Entrepreneurial attitude and entrepreneurial self-efficacy also play a significant role in mediating the effect of entrepreneurial education on entrepreneurial intention in Indonesia's Z generation. Entrepreneurial attitude has a significant role in mediating the effect of entrepreneurial self-efficacy on entrepreneurial intention